IMPROVED MANAGEMENT OF INFORMATION AND INNOVATION TECHNOLOGIES IN THE INDUSTRIAL CLUSTER - Ekaterina A. Naryzhnaya; Vladimir N. Ryabov; Vasilisa S. Tsygankova (Вестник Северо-Кавказского федерального университета)
In the article the necessity of application of information technologies in the process of management of socio-economic systems in the industrial cluster for innovative development. Grounded features of the development of information and communication technologies market introduction in the practice of industrial enterprises.